Overview of Socio-economic Indicators in Area Affected the 2004 Aceh Tsunami Post-Humanitarian Assistance: A Review of Increasing Economic Growth Towards Sustainable Environmental Development - Wahyuningsih, Yayuk Eko; Saukani, Mohd Nasir Mohd; Salleh, Norlida Hanim Mohd (GMPI Conference Series, 2024)
This study aimed to analyze the overview of the impact of socio-economic indicators and the economy of areas exposed to the 2004 Aceh tsunami in the South-western region of Aceh Province, namely West Aceh district, Simeulue district, Nagan Raya district and Aceh Jaya district after five years humanitarian assistance on economic growth towards sustainable environmental development. The study used secondary data with panel data that was collected from Central Bureau of Statistics of Aceh Province and Bank Indonesia of Banda Aceh branch, each of which was obtained over a period of 13 years from 2010 to 2022. While multiple linear regression is employed as a quantitative method for data analysis. The study findings that indicate that indicator of socio, the poverty has a significant effect on economic growth each with a value 0,0782 with significance level of α = 10%.   Meanwhile, the economic indicator, namely inflation, haven’t a statistically significant impact of 0.6517 on economic growth at a significance level of α = 5% or α = 10%. The equation of this model is obtained EG = 0,6797+3,3654LnTP-0,0365INF+ε. Next, the correlation coefficient is 0.0652 and determination coefficient is 0,0271, with value of ttest 1,798836 for total poverty and 0,454205 for inflation as well as Ftest value is 1,709245. However, after the 2004 Aceh earthquake and tsunami disaster, poverty rates have been reduced, but only in the medium term (5-6 years) and currently the condition of the poor population is almost continuously improving. It’s recommended that the regional and Acehnese and central governments recommend various social programs to overcome poverty and also in terms of population. The long-term impact is economic growth continues to rise and facilitates the process of developing a sustainable environment so that it will be better in the future.